OPTIMALIZING THE ROLE OF FISHERIES EXTENTION WORKERS IN FRESHWATER AQUACULTURE IN EAST BALIKPAPAN SUB-DISTRICT AT BALIKPAPAN CITY - Sugiharto, Eko; Purnamasari, Elly; Indratno Gunawan, Bambang (Jurnal Perikanan Unram, 2024)
The aim of this research is to assess the role of fisheries extension in the development of catfish farmer groups in East Balikpapan Subdistrict. The study was carried out from January to March in East Balikpapan Subdistrict, Balikpapan City, using a census sampling method. Data were analyzed using a quantitative descriptive approach with a Likert scale model. The findings indicate that the role of fisheries extension agents in the business development of catfish farming can be evaluated both partially and cumulatively. Partially, the role of extension agents is categorized as "Medium," with the following interval scores for each indicator: motivator at 9.47, educator at 9.79, catalyst at 9.32, organizer at 9.21, communicator at 8.42, and advisor at 9.79. Cumulatively, the role of extension agents in group development is also at a "Medium" level, with a score of 56. According to the catfish farmer groups, the role of extension agents in improving business productivity is deemed sufficiently effective in helping farmers enhance their cultivation skills toward better and more productive outcomes.